Fracture evolution in steel fiber reinforced concrete (SFRC) of tunnel under static and dynamic loading based on DEM-FDM coupling model - Yu Chen; Dongfeng Yu; Yixian Wang; Yanlin Zhao; Hang Lin; Jingjing Meng; Haoliang Wu (International Journal of Coal Science & Technology)
Abstract The frequent or occasional impact loads pose serious threats to the service safety of conventional concrete structures in tunnel. In this paper, a novel three-dimensional mesoscopic model of steel fiber reinforced concrete (SFRC) is constructed by discrete element method. The model encompasses the concrete matrix, aggregate, interfacial transition zone and steel fibers, taking into account the random shape of the coarse aggregate and the stochastic distribution of steel fibers. It captures microscopic-level interactions among the coarse aggregate, steel fibers, and matrix. Subsequently, a comprehensive procedure is formulated to calibrate the microscopic parameters required by the model, and the reliability of the model is verified by comparing with the experimental results. Furthermore, a coupled finite difference method-discrete element method approach is used to construct the model of the split Hopkinson pressure bar. Compression tests are simulated on SFRC specimens with varying steel fiber contents under static and dynamic loading conditions. Finally, based on the advantages of DEM analysis at the mesoscopic level, this study analyzed mechanisms of enhancement and crack arrest in SFRC. It shed a light on the perspectives of interface failure process, microcrack propagation, contact force field evolution and energy analysis, offering valuable insights for related mining engineering applications.